OPTIMALISASI PENGGUNAAN FAKTOR PRODUKSI USAHATANI JAMUR MERANG DI DESA GLAGAHWERO KECAMATAN PANTI KABUPATEN JEMBER - Rizky Yanuarti; Joni Murti Mulyo Aji; Rudi Hartadi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
Glagahwero is one of the largest mushroom producers in Jember, though still lack of production. This research aims to determine factors of production, optimization of production factors, and profit by using optimal production factor. This research was conducted in Glagahwero Village with 32 samples of mushroom farmer. The samples were selected using total sampling method. Data were analyzed using cobb douglas production function to know the factors that significantly influence the production and value of the optimum input use of mushroom farming, and profit analysis to know the comparison of profit value by using the optimum production factor. The results showed that the area of kumbung, seedlings, straw and labor significantly influenced the production of mushroom in Glagahwero but the use of those factors were not optimal (ratio of NPMxi / Pxi 1), it is necessary to add the amount of production factor use to reach optimal value. The value of profit by using the optimal production factor will be greater than using the actual production factor. The results of this study then become basis in conducting mushroom farming in Glagahwero Village optimally by taking into account the amount of input that use.